english: english - Permatasari, Yofi; Silalahi, Wilma (Journal of Business, Management, and Social Studies, 2025)
This research aims to obtain research results on Daya Anagata Nusantara in relation to strategic investment reforms for Indonesia’s economic growth. The author uses normative research with the aim of obtaining analysis results based on legal rules, legal principles by analyzing problems with descriptive research. The existence of Danantara as an Investment Management Agency (BPI) provides a new change in terms of national strategic investment management. The establishment of Danantara is a strategic investment reform that is expected to be able to maximize state assets as a form of directed investment based on strong law. The existence of Danantara can have a significant impact that can potentially increase the layers of hierarchy that can extend the bureaucratic process. By employing normative research grounded in legal rules and principles and applying it to the practical context of Danantara, the research offers a novel bridge between legal theory and real-world strategic investment reform in Indonesia. It likely explores how specific legal frameworks underpin and potentially shape the effectiveness of Danantara.